KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA MAN 1 TAKENGON. - Kausara Usman, Yusrizal, Sakdiah Ibrahim. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: The principal is the spearhead of a school institution, and as a headmaster also in demand to improve the performance of the teacher, because the teacher increases performance will bring a positive impact on a school that dipimpinnya..Dalam this study authors used a qualitative method, is based titles and authors describe research questions and research uses qualitative research patterns with descriptive methods. Data collection techniques in qualitative research data collection is done in a natural setting (natural conditions), the primary data source and data collection techniques more on participant observation (participan observation), in-depth interviews (in-depth interviews) and documentation.Subject of the study come from those contained in the school organization that principals, teachers, supervisors, and school committee at MAN 1 Takengon. This study aimed to obtain data about the managerial competence of the head of Madrasah Aliyah Negeri 1 Takengon in implementing performance improvement guru-guru.Sedangkan specifically research aimed to get the data that is complete, accurate and up to date on: (a) the ability of headmaster in preparing performance improvement program MAN 1 teacher at Takengon, (b) Ability headmaster in developing madrasah organization in MAN 1 Takengon that support improved teacher performance, (c) the ability of headmaster in melaksankaanakan leadership to improve kineja madrassa teachers on MAN 1 Takengon. From the research that found that (a) the Head of madrasah capable in preparing teacher performance improvement program at MAN 1 Takengon, (b) Head madrasah madrassa able to develop the organization in MAN 1 Takengon that support improved teacher performance, (c) Head of madrasah capable melaksankaanakan leadership in the madrasah to improve kineja teacher at MAN 1 Takengon.Keywords: Managerial Skills / Teacher PerformanceAbstrak: Kepala sekolah merupakan ujung tombak dari sebuah lembaga sekolah, dan sebagai kepala sekolah juga di tuntut untuk meningkatkan kinerja guru, karena dengan guru meningkat kinerjanya akan membawa dampak positif bagi sebuah sekolah yang dipimpinnya..Dalam penelitian ini penulis menggunakan metode kualitatif, ini berdasarkan judul maupun pertanyaan penelitian yang penulis jabarkan dan Penelitian ini menggunakan pola penelitian kualitatif dengan metode deskriptif.Teknik pengumpulan data pada penelitian kualitatif pengumpulan data dilakukan pada natural setting (kondisi alamiah), sumber data primer dan teknik pengumpulan data lebih banyak pada observasi berperanserta (participan observation), wawancara mendalam (in depth interview) dan dokumentasi.Subjek penelitian bersumber dari orang-orang yang terdapat dalam organisasi sekolah yaitu kepala sekolah, guru, pengawas, dan komite sekolah pada MAN 1 Takengon. Penelitian ini bertujuan untuk mendapatkan data tentang kompetensi manajerial kepala Madrasah Aliyah Negeri 1 Takengon dalam melaksanakan peningkatan kinerja guru-guru.Sedangkan secara khusus penelitian bertujuan untuk mendapatkan data yang lengkap, akurat dan terkini tentang : (a) Kemampuan kepala madrasah dalam menyusun program peningkatan kinerja guru pada MAN 1 Takengon, (b) Kemampuan kepala madrasah dalam mengembangkan organisasi madrasah pada MAN 1 Takengon yang mendukung peningkatan kinerja guru, (c) Kemampuan kepala madrasah dalam melaksankaanakan kepemimpinan madrasah untuk meningkatkan kineja guru pada MAN 1 Takengon. Dari hasil penelitian yang di temukan bahwa (a) Kepala madrasah mampu dalam menyusun program peningkatan kinerja guru pada MAN 1 Takengon, (b) Kepala madrasah mampu dalam mengembangkan organisasi madrasah pada MAN 1 Takengon yang mendukung peningkatan kinerja guru, (c) Kepala madrasah mampu dalam melaksankaanakan kepemimpinan madrasah untuk meningkatkan kineja guru pada MAN 1 Takengon.Kata kunci :Keterampilan Manajerial/Kinerja Guru.